THE IMPACT OF CORPORATE GOVERNANCE MECHANISM ON THE ASYMMETRIC INFORMATION - Purwanti, Titik (Kiat Bisnis, 2013)
This research aims to analyze the impact of Corporate Governance mechanism on asymmetric information. Corporate Governance mechanism is the subject which protect investor from asymmetric information. The sampling method in this research uses purposive sampling which selected sample by the criteria. They are companies which the 10th highest rank of IICG from 2004-2007. The analysis used descriptive statistics, classic assumption test and multiple regression analysis. The result shows the Corporate Governance mechanism has the significant impact on asymmetric information. The Corporate Governance index and managerial ownership have negative impact on asymmetric information. It shows that the increasing of Corporate Governance index and managerial ownership will decrease the asymmetric information. The institutional ownership board of commisioner composition and size have not negative impact on asymmetric information significantly. Keywords : Corporate Governance Mechanism, Corporate Governance Index, Asymmetric information